Pengaruh Pemusatan Perhatian (Mindfulness) terhadap Koping Keluarga Pasien Skizofrenia - Kadek Ria Hendriyani; I Gede Widjanegara; I Nengah Sumirta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
The addition of the role of caring for patients at home can cause a burden on the family. If the family is burdened, it is possible that the family is unable to use adaptive coping. Mindfulness can help families improve effective coping in a more focused way, so this study wanted to find out the effect of mindfulness on the coping of families of schizophrenic patients in the working area of the Abang 1 Public Health Center. The population in this study were families with one family member experiencing Schizophrenia in the working area of the Abang 1 Health Center with a total number of family members experiencing schizophrenia recorded 66 families with the sample used, namely 34 respondents. The research design that has been carried out uses a pre-experimental design. This study has used the one-group pre-post test design approach. The research sampling technique that has been used is the non-probability sampling technique with purposive sampling. The type of data collected in this study is divided into 2, namely primary data and secondary data. The instrument used was a questionnaire that was distributed online in the form of a Google form. The data analysis used was correlative analysis, and the bivariate analysis used was the paired t-test test. The pre-test results showed that the majority of respondents had family coping included in the maladaptive category of 58,8%. The results of the post-test are that all respondents (100%) have family coping included in the adaptive category. The significance value is 0.000 (p less than0.05), which means that there is an effect of providing mindfulness interventions on family coping.